PERIODICITY OF EARTHQUAKES IN THE CASPIAN SEA - Piriyev, R. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The Caspian Sea is the largest closed reservoir in the world. The strongest earthquake in the Caspian Sea was the 7.9 magnitude, the 1895 Krasnovodsk earthquake. The parameters of earthquakes with different magnitude in recent years in the Caspian Sea were analyzed and the characteristic depth was determined based on statistical data. Attempts to determine their periodicity and attempts to predict for the future have been made on the basis of statistical data of earthquakes occurred within the last 50 years in the Caspian Sea and surrounding regions. In the data taken from the earthquake catalog, parameters of earthquakes whose magnitude is above 5.0 were used. In recent years, earthquakes with a magnitude below 5.0 have been accompanied in the Caspian Sea. The characteristic depth of earthquakes is considered ±60 km. The probability of recurrence of an earthquake with a magnitude of 6.8 occurred in 2000 is likely to occur in 2050.
Keywords: Caspian Sea; earthquake; magnitude; depth; seismicity